ZERO-P IMPLANTS IN CERVICAL SPINE PROCEDURES-CASE REPORT - Taushanov, Mihail; Mitev, Konstantin; Mladenovski, Sasho; Shuntov, Blagoj (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Supplementing anterior cervical disectomy and fusion (ACDF) with plates enhances stabilization, increases fusion and reduces failure rates. Zero-P implant for stand-alone anterior interbody fusion procedures of the cervical spine was recently developed to avoid complications associated with anterior cervical plates Key words: ACDF, HDI, pressure, neck pain, parestesis.